2016
DOI: 10.3141/2572-04
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Natural Gas Vehicles: Financially Viable Option?

Abstract: Natural gas vehicles are being developed because of increasing concerns about energy dependence, air quality and emissions, and, more recently, climate change. The major advantage of natural gas vehicles is their lower fuel cost. Several economic and technical factors such as limited range and availability of relevant infrastructure prevent widespread adoption of natural gas vehicles. A model for the financial analysis of the possibility of compressed natural gas (CNG) vehicles being competitive with gasoline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several empirical studies have addressed the role of endogeneity (in either form) in transportation planning, ranging from general demand and supply frameworks to different aspects of travel behavior, including safety (21,22), vehicle ownership and fuel consumption (23)(24)(25)(26)(27)(28), urban form and residential location impacts (14,(29)(30)(31), and activity scheduling and time use (32).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several empirical studies have addressed the role of endogeneity (in either form) in transportation planning, ranging from general demand and supply frameworks to different aspects of travel behavior, including safety (21,22), vehicle ownership and fuel consumption (23)(24)(25)(26)(27)(28), urban form and residential location impacts (14,(29)(30)(31), and activity scheduling and time use (32).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 3 ] Powered by low‐cost NG (28–57% the price of gasoline for the same energy content), [ 23–25 ] natural‐gas‐fueled vehicles (NGVs) can meet demands for transportation while releasing cleaner emissions than gasoline. [ 26,27 ] Specifically, a vehicle running on compressed natural gas (CNG) emits 70% less carbon monoxide, 87% less nonmethane organic vapors, and 20% less CO 2 than a vehicle running on gasoline. [ 26 ] In addition, NGVs have decreased cold‐start emissions, off‐cycle emissions, evaporation emissions, and running‐loss emissions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] In addition, NGVs have decreased cold‐start emissions, off‐cycle emissions, evaporation emissions, and running‐loss emissions. [ 27,28 ] Yuan et al. [ 29 ] found that even after accounting for methane leakages across the NG supply chain, NGVs (namely passenger cars, transit buses, and heavy‐duty trucks) emit less greenhouse gas throughout their lifecycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of a major city and its population growth together invariably impacts transportation, society, and ultimately all individuals. Transportation issues, including congestion and increased vehicle emissions, can be mitigated with careful planning (Heaslip et al, 2015;Soltani-Sobh, 2015;Soltani-Sobh et al, 2016;Motamed, 2016;Sharifi and Shabaniverki, 2016) but the end is an inescapable truth; the transportation infrastructure can only serve a finite volume of users at a given time.…”
Section: Introductionmentioning
confidence: 99%